2017
DOI: 10.1002/jsfa.8535
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of borage oil with blends of milk protein, β‐glucan and maltodextrin through spray drying: physicochemical characteristics and stability of the microcapsules

Abstract: The results of the present study demonstrate that the CAS-GLU-MD blend is appropriate for microencapsulating borage oil. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
(108 reference statements)
0
7
1
Order By: Relevance
“…However, it is difficult to incorporate the oil into foods because it is very unstable and insoluble in water. This issue could be overcome by using microencapsulation techniques . Besides reducing oxidative deterioration of bioactive compounds, appropriately controlled release of the compounds can also be achieved by microencapsulation .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to incorporate the oil into foods because it is very unstable and insoluble in water. This issue could be overcome by using microencapsulation techniques . Besides reducing oxidative deterioration of bioactive compounds, appropriately controlled release of the compounds can also be achieved by microencapsulation .…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content was higher for the powders with 1 and 2% of β -glucan, than in the 3% ratio of β -glucan powder. The research on the use of microencapsulation using milk proteins and MD or mixture of MD + BG as wall material indicates, that adding beta-glucan might reduce the moisture content [27]. Mahdavi et al [14] showed that shorter chains and more hydrophilic groups result in binding with water from the air after drying in Arabic gum and maltodextrin.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on the potential of combination of milk protein sodium caseinate or whey protein concentrate with beta-glucan or MD as wall materials to encapsulate borage oil by spray drying indicates, that wall material components affect the particle size. Milk proteins sodium caseinate (lower molecule size) with beta-glucan possesses more flexible structure, which successfully covered and stabilized a greater interfacial area, which resulted in smaller particle size, than beta-glucan with whey protein concentrate combination (higher molecule size) [27]. Moreover, Tonon et al [24], in their investigation on microencapsulation of spray-dried açai juice produced with different carrier agents with dextrose equivalent (DE), also observed that particle sizes are related to the molecule size of each carrier agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suitable bulk density is beneficial to reduce the processing costs of the product. The bulk density of MEFO was 0.36 g/ml, which is slightly higher than other similar oil microcapsules, indicating that it has good properties such as flowability (Asensio et al, 2017;Li & Shi, 2018;Li et al, 2013).…”
Section: Moisture Content and Bulk Densitymentioning
confidence: 86%